A diversidade críptica da comunidade zooplanctônica em lagoas intermitentes do semiárido brasileiro: avaliação dos mecanismos de resiliência a alterações ambientais - Santos, Felipe Antonio dos (2023)
The zooplankton community plays a highly relevant role in temporary freshwater ecosystems. Comprising various groups of organisms such as rotifers, cladocerans, copepods, and other microcrustaceans, including Anostraca and Conchostraca, this community plays a vital role in maintaining the health and stability of these environments. It acts as a key link in energy flow and nutrient cycling, connecting different trophic levels and influencing the dynamics of aquatic ecosystems. In this study, we investigated the dynamics and resilience of the zooplankton community in temporary ponds located in the semi-arid region of Pernambuco. Our main objective was to evaluate the impact of different environmental conditions, such as soil type and trophic state of the ponds, on this community. In the first article, we identified that both soil type and trophic state of the ponds exert a significant influence on the presence or absence of various zooplankton species. These findings revealed that some species occur preferentially in clearer environments, while others prefer turbid environments. In the second article, we analyzed the hatching rates of resting forms and the resilience of the zooplankton community, which were influenced by the depth and soil type of the ponds. Remarkably, ponds with rocky soil exhibited a higher hatching rate compared to ponds with clayey soil. We also found that the difference in the composition of hatched organisms increases as the depth of the pond increases. In the third article, we investigated how the hatching rate of the dormant zooplankton community is affected by land use and occupation in the surrounding areas of the ponds. We found that human impact near temporary ponds is directly related to a lower hatching rate of the dormant community, especially in more impacted environments. This research provided a comprehensive insight into the dynamics of the zooplankton community in temporary ponds in the semi-arid region of Pernambuco, highlighting the importance of environmental conditions such as soil type and trophic state of the ponds in the initial composition and temporal succession of communities.